ANALISIS KESULITAN BELAJAR SISWA SMP KELAS VIII DALAM MENYELESAIKAN SOAL ARITMATIKA DI TINJAU DARI KEMAMPUAN KOMUNIKASI MATEMATIS - Desi Tri Lestari; Eka Senjayawati; Euis Eti Rohaeti (Journal on Education, 2019)
The purpose of this study was to describe the learning difficulties of mathematics experienced by students in terms of mathematical communication skills. This type of research is descriptive with a qualitative approach. The subjects in this study were 29 seventh grade 1 Junior High School students. The data collection technique in this study uses a question instrument that is given in the form of a written test, while the data analysis techniques in this study are data collection, data processing, data presentation and conclusion drawing. So the conclusion that can be drawn from this research is that there are 2 difficulties in learning mathematics students, namely; (1) the difficulty of the concept, and (2) verbal difficulties. The causes of these difficulties are due to students' low mathematical communication skills.